Análisis del stock del capital humano para los grandes aglomerados de la Argentina - Gabriel Amós Fridrij (Colegio de Economistas de A Coru\~na, 2008)
– The objective of this paper is to describe the change in the stock of human capital, between 1995 and 2006, as measured by levels of formal education attained by the economically active population (PEA), for large agglomerates of Rosario, Tucuman, Mendoza , and GBA Cordoba of Argentina and also to Salta. Then compare the relative performance of the province of Tucuman with them. It also discusses the incomes of the different levels of human capital accumulated per year per province. It also raises theoretical conducted an econometric model with the aim of explaining what are the factors that determine the differences in the performance of each province. Finally presents conclusions that emerge from the analysis.
Keywords: 330; stock de capital humano; ingreso; población económicamente activa